Strategic Planning for Student Guidance Information System Design in Tourism Department using Ward and Peppard Framework - Yerik Afrianto Singgalen (Journal of Information System and Informatics, 2023)
This study examines the challenges faced by students during the thesis completion process, including miscommunication, document loss, and difficulty scheduling guidance sessions. To address these issues, Ward and Peppard's method was utilized to design a strategic plan for the Tourism Department at Atma Jaya Catholic University of Indonesia. The research findings reveal that the implementation of the student guidance information system, "SIBIMA," results in an efficient and effective process for student registration, supervisor verification, document upload/download, manuscript correction, and monitoring of student progress. Furthermore, the SWOT analysis, Value Chain, Critical Success Factor (CSF), Porter Five Forces model, and McFarlan Grid Portfolio demonstrate that SIBIMA effectively utilizes strengths to overcome weaknesses and minimize threats.